Integrating Circular Economy Through Refuse, Rethink and Reduce in Vocational Education for Sustainable Development - Ab Hamid, Norzaharah; Mohd Kamaruzaman, Fathiyah; Suradin, Salwa; Rasul, Mohamad Sattar; Nik Othman, Nik Norlaili Jamilah (Journal of Technical Education and Training, 2025)
Advancements in sustainable development have expanded into vocational education, highlighting the teaching of circular economy as pivotal in realizing the global vision for Sustainable Development Goals. However, there is no specific tool used to study the smarter product consumption and manufacturing in circular economy management, especially in refuse, rethink, and reduce constructs, as detailed in the 9R circular economy framework, has prompted the current study to conduct a preliminary study throughout the instrument's development and validation. The determination of content validity occurs at two levels; instrument development, and instrument validation. This study aims to obtain item-level content validity index (I-CVI) and scale-level content validity index (S-CVI) for instrument to evaluate smarter product use and manufacture in teaching circular economy. Findings from the first research question indicated that there was agreement on 39 of 44 items (I-CVI at least 0.83), while 5 items did not meet the CVI cutoff value from the six experts who validated the instrument, were subject to revision. The instrument's overall item-level content validity index (I-CVI) for all three constructs is 40.00. The second research question revealed an S-CVI value (on average) of 0.91 for the entire session, with an S-CVI (Universal Agreement) of 0.57. In conclusion, the completed 39-item instrument demonstrates content validity and holds potential for enhancing evaluation efforts on smarter product use and manufacture (refuse, rethink, and reduce) in teaching circular economy for vocational education.